Concurrent Total Colonic Aganglionosis and Esophageal Atresia With Tracheoesophageal Fistula: The First Case Report. (21st September 2018) - Cordeiro-Rudnisky, Fernanda; Whyte, Christine; Sheuka, Natallia; Boguniewicz, Ann; Lee, Hwajeong
Abstract: Introduction: Whether total colonic aganglionosis (TCA), defined as aganglionosis involving the entire colorectum and up to 50 cm of the distal ileum, is within the spectrum of Hirschsprung disease (HD) or not is controversial. There are only three case reports of concurrent colonic HD and esophageal atresia with tracheoesophageal fistula (EA-TEF) in the literature. TCA associated with EA-TEF has not been documented. Methods: A female infant, born at term to a 26-year-old woman, was diagnosed with EA-TEF (gross type C) and was noted to have abdominal distention. The patient continued to have abdominal distention and vomiting following a repair of EA-TEF. A contrast follow-through showed partial obstruction in the distal small bowel. She underwent an exploratory laparotomy with intraoperative rectal biopsies, small bowel resection, and diverting end ileostomy. Calretinin immunohistochemistry was performed on the small bowel resection specimen. Results: The intraoperative rectal biopsies showed an absence of ganglion cells. The exploratory laparotomy revealed a dilated small bowel with a possible transition zone in the ileum, 17 cm from the ileocecal valve. The possible transition zone was resected and the presence of ganglion cells in the proximal margin was confirmed by frozen section. A diverting end ileostomy was created at the resection site. The resected segment of small bowel showed an absence of ganglion cells in the distal portion and a gradual increase of ganglion cells in the proximal portion. Calretinin immunohistochemistry confirmed the presence of calretinin-positive mucosal nerve fibers in the proximal portion. The patient has been eating and gaining weight, without evidence of Down syndrome. Conclusion: We report a first case of concurrent TCA and EA-TEF. Although concurrent HD and EA-TEF is exceedingly rare as well, our case supports a speculation that TCA and HD may share a common pathogenesis, especially when associated with concurrent EA-TEF.